Parameters Optimization of Tuned Mass Damper Using Fast Multi Swarm Optimization - Richard Frans; Yoyong Arfiadi (Institut Teknologi Bandung, 2019)
Tuned mass damper (TMD) has been used for vibration controller of building, especially for high rise building. TMD is one of passive device for reducing response of the structure which subjected to dynamic external disturbance such as wind, or earthquake load. TMD used its weight for reducing the vibration, TMD's frequency has been set with structure's frequency so that the frequency can resonate each other for reducing the response of the structure during the dynamic load. Therefore, three variables have significant effect for TMD performance which are mass ratio of TMD (m), frequency ratio of TMD (a), and damping ratio of TMD (z) which lead to two important variables of TMD properties which are stiffness and damping of TMD. This paper developed an empirical equation for obtaining the optimum parameters of tuned mass damper based on H2 norm control system and fast multi swarm optimization (FMSO). The objective function was to minimize the acceleration and displacement response of the structure. Accelerogram of El-Centro 1940 NS was chosen to be ground motion acceleration for simulating the response of the structure with and without TMD. The result shows a strong correlation both mass ratio of TMD to frequency ratio of TMD and mass ratio of TMD to damping ratio of TMD.Penggunaan peredam massa selaras (PMS) telah banyak digunakan sebagai alat kontrol getaran pada bangunan, khususnya bangunan-bangunan tinggi. PMS adalah salah satu kontrol pasif yang digunakan untuk mengurangi respon getaran dari struktur akibat beban-beban dinamik seperti angin, atau gempa. PMS menggunakan berat sendiri untuk mengurangi getaran, frekuensi dari PMS disesuaikan dengan frekuensi dari struktur sehingga beresonansi satu sama lain untuk mengurangi respon dari struktur selama berlangsungnya beban dinamik. Berdasarkan hal tersebut, ada tiga variabel yang mempunyai efek yang signifikan terhadap performa dari PMS, antara lain: rasio massa PMS (ï), rasio frekuensi PMS (ï¡), dan rasio redaman PMS (ïº) yang akan berhubungan langsung dengan dua parameter penting dari PMS yaitu kekakuan dan redaman dari PMS. Tulisan ini mengusulkan persamaan empirik untuk mendapatkan properti optimum dari PMS dengan menggunakan fungsi kontrol H2 dan algoritma fast multi swarm optimization. Fungsi objektif yang digunakan adalah untuk meminimumkan respon percepatan dan perpindahan dari struktur. Data rekaman El-Centro 1940 NS dipilih sebagai data percepatan tanah dasar untuk mensimulasikan respon dari struktur dengan dan tanpa menggunakan PMS. Hasil menunjukkan terdapat korelasi yang kuat antara rasio massa dari PMS terhadap rasio frekuensi dari PMS serta rasio massa dari PMS terhadap rasio redaman dari PMS.